Reviews opinion search engine (ROSE) - Chew, Kok Soon. (2009)
With this project, we hope to enable users to be able to compare products accurately and have the luxury of checking out the products' reviews from other users, just through our one-stop ROSE web portal. This report documents on improving the labeling process of the reviews and segments in the Review/Opinion Search Engine (ROSE) database. The initial problems and the solutions proposed are included in this report. Some possible competitors and their projects are also highlighted. In order to provide this wonderful web portal to serve the consumers, it is important that the reviews and segments are properly and efficiently labeled. This is to ensure that there is a sufficient quantity of data that is useful and at the same time, spamfree. However, with the humongous amount of data, a good system is needed to prevent time and manpower wastage.